The Relationship Between Mental Health Disorders and Smoking Behavior in Company X - Desy Indah Mardiana; Ratno Adrianto (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The WHO study indicates that over 1.1 billion people globally consumed tobacco in 2023, with significantly higher rates among men than women. Furthermore, the Basic Health Research (Riskesdas) statistics from the Indonesian Ministry of Health in 2023 revealed that approximately 14 million adults aged 15 years and older, constituting 6% of Indonesia's population, suffer from symptoms of anxiety and depression. Anxiety and depression are closely associated with smoking behavior, as higher levels of depression correlate with increased smoking tendencies, and conversely, lower levels of depression correspond with decreased smoking tendencies. Workplace- related depression stemming from job stress, fatigue due to work, and reduced anxiety from work fatigue that affects sleep and concentration difficulties can lead to continuous consumption of cigarettes. Objective : The purpose of this study is to determine the relationship between mental health disorders and smoking behavior at Company X Research Methods/ Implementation Methods : This study employs a quantitative research approach with a cross-sectional design. Data were gathered using a questionnaire. The population for this study consists of employees at Company X, with a sample size of 90 respondents selected through accidental sampling. The instruments utilized in this research include the PHQ-9 (measuring depression levels) and GAD-7 (assessing anxiety levels). Statistical analysis for this study involves Spearman's rank correlation test. Results : The Spearman rank correlation calculation yielded a significant value (Sig.) = 0.000 (p value ≤ 0.05), indicating highly significant data. Therefore, H1 is accepted, suggesting a relationship between smoking behavior and mental disorders among employees at Company X. Additionally, the Spearman rank analysis revealed a correlation coefficient of 0.804, indicating a positive correlation Conclusion/Lesson Learned: Based on the research findings, there exists a relationship between mental disorders and smoking behavior among employees at Company X. Increased smoking correlates with higher levels of depression and anxiety. Future research could further develop by employing different research designs, varying independent variables, and expanding the sample size, thereby advancing research in the field of mental health.